Arbitrary Usage of Procedural Rights: Comparative Analysis, and Applied Study - محمد عبدالله هادي; رؤوف علي سيروان (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The implementation of procedural rights in all its various forms, whether it is formulated in a right, a license, or an authority, aims to achieve the targeted interest. This embodied to serve substantive rights since the aim of procedural right is reaching to substantive right. The lawmaker, in regulating rights and determine its contain as well as granting the authorities to its holders, attempts to reconcile between all public and private interests. Therefore, it is permissible for procedural right holder to use his/her right within the boundary drawn by law. However, the usage of such right should not lead to arbitrariness. If an individual abusively exercises such right and harm the others, he/she will be accountable and must compensate the damage. The question arises is what is the measurement to determine or describe the arbitrariness in exercising such right? Is this recognizable by referring to standards provided by civil law, or the nature of such rights entails to depend on other procedural standards in a way that achieves the goal which the right aimed to obtain. Thus, this study aims to search for standards that the procedural rights depend on, explaining the legislative, judicial, and jurisprudence attitude. In addition, the study intends to explain the factors that motivated the lawmaker to treat with procedural rights in a special way, and then the barriers that impede the courts to step forward toward the progress accomplished in the civil and procedural fields.